2004
DOI: 10.1063/1.1828033
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of segregation in Pt-Ni catalyst nanoparticles

Abstract: We have investigated the segregation of Pt atoms in the surfaces of Pt-Ni nanoparticles, using Modified Embedded Atom Model potentials and the Monte Carlo method. The nanoparticles are assumed to have disordered fcc configurations at two fixed overall concentrations (50 at.% Pt and 75 at.% Pt). We use four kinds of nanoparticle shapes [cube, tetrahedron, octahedron, and cubo-octahedron] terminated by {111} and {100} facets to examine the extent of the Pt segregation to the nanoparticle surfaces and determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
144
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 51 publications
14
144
1
1
Order By: Relevance
“…Therefore, one aim of our investigations for Pt-Ni (fcc-fcc), Pt-Re (fcc-hcp), and Pt-Mo (fcc-bcc) nanoparticles is to establish that the MEAM approach is capable of accurately simulating surface phenomena for a broad spectrum of Pt bimetallic alloy nanoparticles, even when one component might prefer a different lattice. Using MEAM potentials, we have indeed achieved reasonably good simulation results for Pt-rich Pt-Ni [21], Pt-Re [22], and Pt-Mo [23] nanoparticles with the fcc lattices and Re-rich Pt-Re [22] nanoparticles with the hcp lattice.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, one aim of our investigations for Pt-Ni (fcc-fcc), Pt-Re (fcc-hcp), and Pt-Mo (fcc-bcc) nanoparticles is to establish that the MEAM approach is capable of accurately simulating surface phenomena for a broad spectrum of Pt bimetallic alloy nanoparticles, even when one component might prefer a different lattice. Using MEAM potentials, we have indeed achieved reasonably good simulation results for Pt-rich Pt-Ni [21], Pt-Re [22], and Pt-Mo [23] nanoparticles with the fcc lattices and Re-rich Pt-Re [22] nanoparticles with the hcp lattice.…”
Section: Introductionmentioning
confidence: 83%
“…The MEAM potentials for the pure metals (Pt, Ni, Re, and Mo) are developed by fitting parameters to reproduce empirical data for cohesive energies, lattice constants, elastic constants, and vacancy formation energies of fcc Pt, fcc Ni, hcp Re, and bcc Mo [21][22][23]. Moreover, as shown in Table 1, the MEAM potentials for pure metals lead to surface energies of relaxed extended low-index pure surfaces that are in good agreement with first-principles calculations [44] and experimental measurements [45,46].…”
Section: Modified Embedded Atom Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous computational results based on Monte Carlo (MC) simulations have addressed the structural stability of cuboctahedral PtNi NPs, ranging from 2.5 to 5 nm [22]. Using a many-body potential to describe the interactions between metal atoms, MC simulations at 600 K showed that PtNi tends to form surface-sandwich structures, with a segregation pattern in which Pt atoms are enriched at the outermost and third shells, while the Ni atoms are enriched in the second shell.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous experimental and theoretical studies have investigated temperature- [35][36][37][38][39][40][41][42][43][44] and adsorbate-driven [45][46][47][48] segregation process in Pt-Ni systems, including the effect of such segregation in their catalytic reactivity. 35,37,[49][50][51][52] In general, segregation phenomena in bimetallic systems can be understood based on the surface energies and atomic radius of the two metals, with the element having a larger atomic radius and a lower surface energy segregating towards the free surface.…”
mentioning
confidence: 99%